Electrochemical deposition of Bi2Te3 for infiltrating into patterned templates - Zhao, Junnan. (2010)
Bi2Te3-based materials are the most promising thermoelectric (TE) materials for near room temperature applications and currently being used for fabricating commercial TE devices. However, the higher ZT achieved so far for Bi2Te3-based materials still remains around 1.0. ZT is expected to improve by designing phononic structure which can reduce thermal conductivity but not affect the electrical conductivity. Cost-effectiveness and relative ease in controlling the experimental parameters make electrochemical deposition (ECD) on templated substrates an attractive process for the synthesis of novel structures. This work was divided into two parts. The first part established the optimum deposition conditions which were then used for depositions on templated substrates. Two series of Bi2Te3 films were deposited with varying potential (-0.1V, -0.2V, -0.3V, -0.4V)and varying film thickness (1μm and 2μm) respectively via pulsed ECD on sputtered Bi2Te3 conductive layer to study the effect of various potentials and film thickness on TE properties. The optimized conditions were then used to infiltrate Bi2Te3 into commercial templates, so as to determine the suitability of ECD for future infiltration into phononic templates. The deposited films exhibited higher electrical conductivity and lower Seebeck coefficient as compared to sputtered Bi2Te3 conductive layer. A peak power factor of 1.05×10-3 W/m.K2 was achieved in the film deposited at potential of -0.1V with 2μm thick, which was contributed to the large increase in electrical conductivity. Infiltration of Bi2Te3 into AAO and PC templates was conducted at potential of -0.1V, determined by results obtained in the first part of the project. High yielding rates were achieved in both AAO and PC templates. It is predicted that Bi2Te3 can be infiltrated successfully into phononic templates to create phononic structure when phononic templates can be finally created in the future work.